The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1017/s0950268899002423
|View full text |Cite
|
Sign up to set email alerts
|

Cowpox: reservoir hosts and geographic range

Abstract: It is generally accepted that the reservoir hosts of cowpox virus are wild rodents, although direct evidence for this is lacking for much of the virus's geographic range. Here, through a combination of serology and PCR, we demonstrate conclusively that the main hosts in Great Britain are bank voles, wood mice and short-tailed field voles. However, we also suggest that wood mice may not be able to maintain infection alone, explaining the absence of cowpox from Ireland where voles are generally not found. Infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
194
2
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(207 citation statements)
references
References 22 publications
3
194
2
8
Order By: Relevance
“…In Great Britain, antibody has been found occasionally in house mice but the highest seroprevalence is in bank voles, wood mice, and field voles, and these species are believed to be the reservoir hosts [6]. Cowpox does not cause obvious clinical signs or increase mortalities in voles or mice in the laboratory [3], experimental studies have demonstrated that cowpox can affect fecundity by delaying the onset of reproduction [15].…”
Section: Establishment Of Vlvs In Naturementioning
confidence: 99%
“…In Great Britain, antibody has been found occasionally in house mice but the highest seroprevalence is in bank voles, wood mice, and field voles, and these species are believed to be the reservoir hosts [6]. Cowpox does not cause obvious clinical signs or increase mortalities in voles or mice in the laboratory [3], experimental studies have demonstrated that cowpox can affect fecundity by delaying the onset of reproduction [15].…”
Section: Establishment Of Vlvs In Naturementioning
confidence: 99%
“…Wild rodents are considered the main reservoir hosts [5], although human transmission often occurs from companion animals such as rats and via intermediate domestic pets such as cats [40]. In wild rodents, the highest seroprevalence has been recorded in bank voles, wood mice (Apodemus sylvaticus), and field voles (Microtus agrestis) [2,7,18,12]. Human OPV infection is rare and usually produces a localized lesion on the fingers, hands, or face [33].…”
Section: Introductionmentioning
confidence: 99%
“…Small rodents, such as voles and mice, are considered a natural reservoir. No transmission between humans has been reported so far [1][2][3].…”
Section: Introductionmentioning
confidence: 94%
“…Cowpox virus belongs to genera orthopoxvirus -a heterogeneous group of viruses that infect a broad spectrum of wild rodents and domestic animals, but seem to be restricted to the Old World [2,3].…”
Section: Introductionmentioning
confidence: 99%